The Problem with Post-Work: Work and the Work Ethic as Units of Historical Analysis. (5th December 2018) - Resnikoff, Jason
Abstract : "Work means everything to us, " James Livingston writes in the introduction to his recent book, No More Work: Why Full Employment Is A Bad Idea . The meaning of work, what Livingston calls the work ethic, is our problem. "And we've believed that, even if it sucks, a job gives meaning, purpose and structure to our everyday lives—at any rate, we're pretty sure that it gets us out of bed, pays the bills, makes us feel responsible, and keeps us away from daytime TV." The time for this mode of thinking, we learn, has passed. "These beliefs are no longer plausible, " Livingston says. "In fact, they've become ridiculous, because there's not enough work to go around, and what there is of it won't pay the bills."